Influence of Volitional Competencies on Achievement Goals of People with Physical Disability in Physical Activity Settings - Proios Ioannis (Sciendo, 2020)
This study's purpose was to investigate any possible relationship between the goal perspectives (task and ego orientation) and volitional competences (persistence, expedience, and purposefulness) in physical activities settings. Participants were 134 people with a physical disability (103 men and 31 women) with age ranging from 14 to 67 years. All participants participated in physical activities. Participants filled out the Measure Athletes' Volition - Short (MAV-S), and Task and Ego Orientation in Sports Questionnaire (TEOSQ). Results revealed that volitional competencies are predictors goal perspectives in physical activity settings. In addition, the findings showed that the expedience is a stronger predictor to task orientation, while persistence competence is to ego orientation. In conclusion, the present study is considered to offer new knowledge on the achievement goal orientation people with physical disabilities in physical activity contexts. The first one is that volitional competencies (expedience and purposefulness) are significantly positive predictors of task orientation. The second conclusion is that persistence competence is significantly positive predictor, while purposefulness competence is negative predictor of ego orientation.